2008
DOI: 10.1158/0008-5472.can-08-2144
|View full text |Cite
|
Sign up to set email alerts
|

NORE1B Is a Putative Tumor Suppressor in Hepatocarcinogenesis and May Act via RASSF1A

Abstract: Recently, we found epigenetic silencing of the Ras effector genes NORE1B and/or RASSF1A in 97% of the hepatocellular carcinoma (HCC) investigated. This is strong evidence that the two genes are of major significance in hepatocarcinogenesis. Although RASSF1A serves as a tumor suppressor gene, the functions of NORE1B are largely unknown. Here, we studied the role of NORE1B for growth and transformation of cells. To understand the molecular mechanisms of action of the gene, we used the wild-type form and deletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Images were acquired with filters for CFP (cyan), YFP (yellow), and for FRET using identical microscope and camera settings. After determination of the correction factor for CFP (donor) and YFP (acceptor), the intensity of the FRET signal (green) was calculated [25]. Representative examples are shown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Images were acquired with filters for CFP (cyan), YFP (yellow), and for FRET using identical microscope and camera settings. After determination of the correction factor for CFP (donor) and YFP (acceptor), the intensity of the FRET signal (green) was calculated [25]. Representative examples are shown.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence resonance energy transfer (FRET) analysis was performed as described previously [25]. For quantitative analysis calculated FRET images were exported and analysed using ImageQuant software.…”
Section: Fluorescence Resonance Energy Transfermentioning
confidence: 99%
“…A loss-of-function experiment revealed that loss of RASSF5 leads to uncontrolled growth and transformation of HCC, but overexpression of RASSF5 suppresses cell replication and transformation (22). RASSF5 is suppressed in pheochromocytoma and abdominal paraganglioma, resulting in enhanced apoptosis and impaired colony formation (23).…”
Section: Discussionmentioning
confidence: 99%
“…For example, expression of both AKR1B10 and RASSF1 has been reported to be related to the prognosis of human tumors including HCC. [21][22][23][24][25][26][27] Hierarchical clustering of gene expression separated HCC patients into 2 subclasses, with a striking survival difference between subclasses (P \ 0.0001) (Fig. 3a, b).…”
Section: Survival Analysis Using Data From Tumor-adjacent Liver Tissuementioning
confidence: 98%